FUNCTIONS AND OBJECTIVES OF THE COMPONENTS OF DEFENSE IN THE SYSTEM OF PROTECTION OF DEFENSE OF THE STATE - Пашинський, Володимир Йосипович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: to consider and resolve the problematic issues of the legislative definition and differentiation of the functions and tasks of the components of the defense forces in the context of defense reform. Methods of research: application of general scientific and special legal methods of cognition allowed to solve the scientific task of legislative regulation of the functions and tasks of the components of the defense forces in modern conditions. Results: the problem issues of the legal regulation of the functions and tasks of the components of the defense forces are investigated by the current legislation and definitely the uncertainty and directions of their solution during the defense reform are investigated. Discussion: in today’s conditions, «hybrid» challenges and threats in the defense field, the establishment of an effective system of defense of the state is possible only on the basis of a clear division and legislative consolidation of the functions, tasks and responsibilities of all components of the defense forces.